2012
DOI: 10.2147/ijn.s35329
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of thymoquinone-encapsulated chitosan nanoparticles for nose-to-brain targeting: a pharmacoscintigraphic study

Abstract: Chitosan (CS) nanoparticles of thymoquinone (TQ) were prepared by the ionic gelation method and are characterized on the basis of surface morphology, in vitro or ex vivo release, dynamic light scattering, and X-ray diffractometry (XRD) studies. Dynamic laser light scattering and transmission electron microscopy confirmed the particle diameter was between 150 to 200 nm. The results showed that the particle size of the formulation was significantly affected by the drug:CS ratio, whereas it was least significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(95 citation statements)
references
References 45 publications
6
83
1
2
Order By: Relevance
“…Gamma scintigraphy was selected as a powerful and rapid method to evaluate the biodistribution of the formulation after nasal administration in rodents. 76 A suspension of simvastatin was used as a control. It is worth pointing out that the radioactivity that is detected cannot be considered permanently bound to the particles or to the drug molecule.…”
mentioning
confidence: 99%
“…Gamma scintigraphy was selected as a powerful and rapid method to evaluate the biodistribution of the formulation after nasal administration in rodents. 76 A suspension of simvastatin was used as a control. It is worth pointing out that the radioactivity that is detected cannot be considered permanently bound to the particles or to the drug molecule.…”
mentioning
confidence: 99%
“…The aforementioned elevation in the percentage change of serum urea and creatinine in the nasal GH solution group might be due to the leakage of a fraction of the nasally administered GH solution to systemic blood circulation via nasal mucosa. However, negligible drug leakage is expected upon applying nasal CX-NP2 because of their mucoadhesiveness (Alam et al, 2012;Md et al, 2013). As it has not been reported previously that GH oral administration might have such elevating effect on serum urea and creatinine levels, the explanation of these results requires further investigation.…”
Section: Groupmentioning
confidence: 91%
“…This might be due to the leakage of a fraction of the nasally administered GH solution to systemic blood circulation via nasal mucosa. The aforementioned leakage is thought to be negligible in case of nasal CX-NP2 because of their superior mucoadhesiveness and permeation to CNS directly (Alam et al, 2012;Md et al, 2013).…”
Section: Groupmentioning
confidence: 99%
“…The EE values for the FDG loaded NP was much higher due to the increased concentration of the bioactive compounds due to freeze drying. Alam et al [28] reported 63% for TQ-chitosin NP whereas 90% was reported for TQ-liposome NP [29]. Many factors influences the control and regulation of the EE such as the: entrapped material, polymer molecular weight, and lactide: glycolide ratio [30] [31] [32], likewise the interaction between the hydroxyl group of the active compound and carboxyl group of the PLGA.…”
Section: Entrapment Efficiencymentioning
confidence: 99%